Time-domain nature of group delay - 王建武 冯正和 (Chinese physics B, 2015)
The characteristic of group delay is analyzed based on an electronic circuit, and its time-domain nature is studied with time-domain simulation and experiment. The time-domain simulations and experimental results show that group delay is the delay of the energy center of the amplitude-modulated pulse, rather than the propagation delay of the electromagnetic field. As group velocity originates from the definition of group delay and group delay is different from the propagation delay, the superluminaiity or negativity of group velocity does not mean the supeduminal or negative propagation of the electromagnetic field.